2007
DOI: 10.1177/154405910708600919
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces Expression and Activation of AMPK in Rat Dental Pulp Cells

Abstract: Rat dental pulp RPC-C2A cells, established and kindly provided by Kasugai et al. (1988), were maintained in minimum essential medium (MEM, Invitrogen, Carlsbad, CA, USA) supplemented with 10% heat-inactivated fetal bovine serum (FBS) and 10 mg/mL kanamycin at 37°C in a humidified atmosphere at 5% CO 2 with 20% O 2 . As hypoxic conditions, cells were cultured in a humidified atmosphere at 5% CO 2 with 2% O 2 . Cell Proliferation AssayCells were seeded in 96-well plates at a density of 5 x 10 4 cells/well and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…The response of DPCs to hypoxia is a complex biological process that contains multiple aspects, including the change of cell basic activity as well as the appropriate inductive molecular signals. The underlying cellular and molecular mechanisms regulating the events reacting to hypoxia have been the targets of a series of investigations (2)(3)(4)(5)(6)(7). Although these studies have provided valuable information about the effects of hypoxia on DPC cell cycle, energy, proliferation, stemness, angiogenic ability, and erythropoietin expression, little information was available regarding DPC mineralization in hypoxia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The response of DPCs to hypoxia is a complex biological process that contains multiple aspects, including the change of cell basic activity as well as the appropriate inductive molecular signals. The underlying cellular and molecular mechanisms regulating the events reacting to hypoxia have been the targets of a series of investigations (2)(3)(4)(5)(6)(7). Although these studies have provided valuable information about the effects of hypoxia on DPC cell cycle, energy, proliferation, stemness, angiogenic ability, and erythropoietin expression, little information was available regarding DPC mineralization in hypoxia.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that short-term hypoxia had effects on the growth of DPCs to induce cell cycle arrest and apoptosis (2). DPCs changed cellular energy status to adapt to hypoxia environment by activating adenosine monophosphate-activated protein kinase (3). However, a long-term hypoxia condition promoted dental pulp stem cell proliferation and maintained their stemness (4).…”
mentioning
confidence: 98%
“…Recent studies have suggested that AMPK plays an important role in the treatment of type 2 diabetes mellitus, protection from apoptosis, and regulation of angiogenesis; exerts antiatherosclerotic effects; and is involved in anti-inflammatory signaling (17,18). Furthermore, the levels of the main AMPK subunit isoform increased time dependently under hypoxia in rat dental pulp cells (19). This suggests that AMPK plays an important role in the reactions of pulp cell to stimuli, presumably in maintaining energy homeostasis.…”
mentioning
confidence: 97%
“…On the other hand, TNF alters AMPK activation by modulating the synthesis of PP2C (Lu et al, 2010;Steinberg et al, 2006). Aside from the rapid control of AMPK activation by phosphorylation, changes in the expression of subunit genes or the turnover of AMPK subunits can help to fine tune AMPK activity in some tissues (Barry et al, 2010;Fukuyama et al, 2007;Hallows et al, 2006;Qi et al, 2008;Niesler et al, 2007;Steinberg et al, 2003).…”
Section: Control Of Ampk Activity By Phosphorylation and Changes In Amentioning
confidence: 99%